The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0246140
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with virological non-suppression among HIV-positive children receiving antiretroviral therapy at the Joint Clinical Research Centre in Lubowa, Kampala Uganda

Abstract: Background While the proportion of HIV-positive children (under 15 years) enrolled on antiretroviral therapy (ART) has increased in recent years, up to 60% of children started on ART do not achieve virological suppression. We set out to determine the factors associated with virological non-suppression among children living with HIV receiving ART at a peri-urban HIV care clinic in Kampala, Uganda. Method This was a retrospective cohort study conducted at the pediatric HIV/AIDS clinic at the Joint Clinical Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 18 publications
3
26
2
Order By: Relevance
“…This selection depends on pharmacological factors, the efficacy of the antiviral treatment, and the genetic barrier of the virus to different ARTs [6]. Previous studies reported that poor adherence to ART, WHO clinical stages III and IV, level of education, co-infection, and certain substances such as nicotine in tobacco, alcohol, and drugs were the main predictors of ART resistance [7][8][9][10][11][12]. A group of researchers has shown that non-nucleoside reverse transcriptase inhibitors (NNRTI) resistance ultimately appears to predict treatment failure in people living with HIV/AIDS (PLHIV) at the start of ART with DTG [13].…”
Section: Introductionmentioning
confidence: 99%
“…This selection depends on pharmacological factors, the efficacy of the antiviral treatment, and the genetic barrier of the virus to different ARTs [6]. Previous studies reported that poor adherence to ART, WHO clinical stages III and IV, level of education, co-infection, and certain substances such as nicotine in tobacco, alcohol, and drugs were the main predictors of ART resistance [7][8][9][10][11][12]. A group of researchers has shown that non-nucleoside reverse transcriptase inhibitors (NNRTI) resistance ultimately appears to predict treatment failure in people living with HIV/AIDS (PLHIV) at the start of ART with DTG [13].…”
Section: Introductionmentioning
confidence: 99%
“…There were also fewer young adolescents in this study on DTGbased regimens compared to older adolescents; however, the numbers were small. This lower VS among young adolescents could stem from a significant proportion of ALHIV in the study having been perinatally infected and thereby experiencing a longer duration of the disease, suboptimal past treatment regimes, potentially more compromised immune system as well as behavioral challenges with adherence such as low treatment self-efficacy, limitations of caregiver treatment literacy, including not understanding side effects, or not being able to attend care appointments due to competing priorities (e.g., like attending school) [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Children aged 10-15 years had the highest rate of viral suppression at 12 months (93% versus 90% aged 5-<10 years and 85% age <5 years), although these differences were not statistically significant. Although viral suppression among older adolescents has been reported to be poor, other pediatric cohorts have reported better viral suppression among young adolescents 10-15 years than younger children (under age 5 years) and older adolescents 15-18 years [16][17][18]. Eswatini had an existing weekend teen HIV support group for adolescents that many of the 10-15 year old children participated in and could have contributed to improved suppression in older children.…”
Section: Discussionmentioning
confidence: 99%